Costing and decision - making in agriculture: an applied proposal (Costos y Gestión, 2025)
Agricultural enterprises face productive dynamics marked by climatic uncertainty,extended biological cycles, and weak correlations between costs, prices, and outputvolumes. In this context, decision-making requires tools that can anticipate scenariosand provide economically sound insights. This paper presents a ten-step variable costing methodology, developed from professional and academic experiences in realagro-productive settings. The proposed approach enhances cost management througha logical and applicable framework that integrates both qualitative and quantitative analysis. It enables the identification of cost objects, classification of cost componentsby behavior, and calculation of strategic indicators such as break-even points, marginal contribution, and sensitivity analysis. A real-world case involving crop production underdifferent operational schemes is included. The methodology offers a practical guide for agricultural professionals, entrepreneurs, and analysts, aiming to strengthen theirability to plan, control, and evaluate economic performance.
Keywords: variable costing; decision-making; break-even point; agricultural enterprises; management analysis